Menstrual Hygiene among Reproductive Age Group Women in a Rural Area, Tamil Nadu - S. Sangeetha Balamurugan; S. S. Shilpa; Sheethal Shaji (Current Practice in Medical Science Vol. 9, 2022)
The purpose of this study is to evaluate menstrual hygiene practices and the impact of socio-demographic factors on menstrual hygiene among women of reproductive age group in a rural area. Menstrual hygiene management should be an imperative part of healthcare to safe guard the reproductive health of women. It is a cross-sectional community-based study that was carried out among 200 women of reproductive age group (15-45 years) in a rural field practice area of VMKV Medical College Hospital, Salem, using a simple random sampling technique. Majority of the study population, 36% (72/200) belonged to the 21-30 years age group. About 75% (150/200) were married. Majority of women 35% (70/200) were unskilled workers, 43.3% (86/200) had primary education and 54.3% (108/200) belonged to lower middle class. The mean age of menarche among the reproductive age-group women was 13.15 years. Majority of women 51.8% (104/200) used cloth during menstruation, about 45.7% (91/200) used the same cloth by washing and reusing every month. Socio-demographic characteristics and hygiene behaviours had a substantial impact on women during menstruation (P < 0.001). It was observed that the majority of rural women were engaged in unhygienic behaviour during menstruation. Hence, efforts should be made to create awareness about using sanitary pads and follow hygienic practices during menstruation,as a part of menstrual hygiene management (MHM) ,along with improving female literacy and general living conditions.